Hubungan Letak Lesi dengan Fungsi Kognitif pada Pasien Stroke Iskemik di RSUD Ulin Banjarmasin - Fuadi Rifqa Shafari; Fakhrurrazy Fakhrurrazy; Didik Dwi Sanyoto Sanyoto (Homeostasis, 2020)
Abstract: Ischemic stroke can cause motor loss, loss of communication, and cognitive impairment. Cognitive is a thought process, namely the ability of individuals to connect, assess, and consider a problem or conversation. Cognitive can be regulated by the location of the lesion. One instrument that can measure cognitive function is the Mini-Mental State Examination (MMSE) with a cognitive score that has a score range of 0-30. The purpose of this study was to analyze the relationship between cognitive function in stroke patients at MMSE in Ulin Hospital Banjarmasin. This research was observational analytic and cross-sectional analytic. MMSE examination is carried out after the respondents meet the inclusion and exclusion criteria. As many as 30 samples obtained by purposive sampling were obtained in cortical as many as 6 respondents, lesions in subcortical as many as 16 respondents, and lesions in basal ganglia as many as 8 respondents. MMSE values for respondents were found with the normal category of 10 respondents, the medium category was 12 respondents and the weight category was 8 respondents. Analysis using the Kormogorov-Smirnoff trial showed no significant value p = 0.841. Conclusions there is no the relationship between the location of the lesion with cognitive function in stroke patients at Ulin Hospital Banjarmasin.. Keywords: ischemic stroke, cognitive function, MMSE, location of lesion Abstrak: Stroke iskemik dapat menyebabkan kehilangan motorik, kehilangan komunikasi, dan gangguan kognitif. Kognitif adalah suatu proses berpikir, yaitu kemampuan individu untuk menghubungkan, menilai, dan mempertimbangkan suatu masalah atau percakapan. Kognitif dapat diatur oleh letak lesi. Tujuan penelitian ini untuk menganalisis hubungan antara fungsi kognitif pada penderita stroke di MMSE di RSUD Ulin Banjarmasin. Penelitian ini analitik observasional dengan pendekatan cross-sectional. Instrumen yang digunakan berupa Mini-Mental State Examination (MMSE) dengan Skor kognitif yang memiliki rentang skor 0-30. Sebanyak 30 sampel diperoleh secara purposive sampling diperoleh pada kortikal sebanyak 6 responden, lesi pada subkortikal sebanyak 16 responden, dan lesi pada ganglia basalis sebanyak 8 responden. Nilai MMSE pada responden ditemukan dengan kategori normal 10 responden, kategori sedang 12 responden dan kategori berat 8 responden. Analisis menggunakan uji coba Kormogorov-Smirnoff menunjukkan nilai tidak signifikan p = 0,841. Kesimpulan tidak terdapat hubungan antara letak lesi dengan fungsi kognitif pada pasien stroke di RSUD Ulin Banjarmasin. Kata-kata kunci: stroke iskemik, fungsi kognitif, MMSE, letak lesi